HEART RATE VARIABILITY ASSESSMENT AND ITS POTENTIAL - Buy Min Ziep; E. O. Taratukhin (Российский кардиологический журнал)
Heart rate variability (HRV) is a new method of non-invasive assessment of functional status, various levels of regulatory systems, and adaptation to internal and external factors. This review describes the development of HRV analysis, its physiological basis, some methodological aspects, and clinical potential.